2002
DOI: 10.1080/14927713.2002.9651310
|View full text |Cite
|
Sign up to set email alerts
|

Leisure and Volunteer Motivation at a Special Sporting Event

Abstract: Volunteering as a form of leisure has been of interest to researchers for some time. This study examines volunteer motivation at a special sporting event in order to identify the links between special event motivations and volunteering as a leisure experience within the context of the work/leisure continuum developed by Cuskelly and Harrington (1997). A questionnaire was administered to volunteers to assess motivation using the Special Event Volunteer Motivation Scale (SEVMS). Analysis revealed four motivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 14 publications
1
69
0
Order By: Relevance
“…Existing studies have often addressed the importance of teamwork in the volunteering sector [54][55][56]. This is especially the case with event volunteering, even if individuals independently participate in volunteering in the event [54]. Supporting this, Doherty (2009) found that volunteer satisfaction is significantly influenced by team members [55].…”
Section: Moderating Roles Of Volunteer Team Cohesiveness Upon the Relsupporting
confidence: 53%
See 1 more Smart Citation
“…Existing studies have often addressed the importance of teamwork in the volunteering sector [54][55][56]. This is especially the case with event volunteering, even if individuals independently participate in volunteering in the event [54]. Supporting this, Doherty (2009) found that volunteer satisfaction is significantly influenced by team members [55].…”
Section: Moderating Roles Of Volunteer Team Cohesiveness Upon the Relsupporting
confidence: 53%
“…One empirical study [53] demonstrated the significant role team cohesiveness plays in increasing the positive effect of employee attitudes toward innovativeness upon knowledge use and new product development performance. Existing studies have often addressed the importance of teamwork in the volunteering sector [54][55][56]. This is especially the case with event volunteering, even if individuals independently participate in volunteering in the event [54].…”
Section: Moderating Roles Of Volunteer Team Cohesiveness Upon the Relmentioning
confidence: 99%
“…The Special Event Volunteer Motivation Scale (SEVMS) (Farrell, Johnston, & Twynam, 1998) is the most widely tested of these scales. It has been applied by Farrell and colleagues to single events: a women's curling championship (Farrell et al, 1998), a scout jamboree (Johnston, Twynam, & Farrell, 1999), and a world junior curling event (Twynam, Farrell, & Johnston, 2002). It has subsequently been tested by other researchers, including Khoo and Engelhorn (2007) at the Malaysian Paralympiad, Reeser, Berg, Rhea, and Willick (2005) at the 2002 Salt Lake City Winter Olympic and Paralympic Games, Grammatikopoulos, Koustelios, and Tsigilis (2006) at YMCA children's summer camps, and an adaptation used by Dickson, Benson, Blackman, and Terwiel (2013) to assess volunteer motives at the 2010 Vancouver Winter Olympic and Paralympic Games.…”
Section: Lockstone-binney Et Almentioning
confidence: 99%
“…In an event-specific context, research (e.g., Doherty, 2009;Downward & Ralston, 2006;Twynam, Farrell, & Johnston, 2002) has also found that individuals who have a good experience while volunteering at an event are more likely to volunteer at future events. For example, 49% of volunteers from the World Junior Curling Tournament (Twynam et al, 2002); 85% of 2002 Commonwealth Games volunteers (Downward & Ralston, 2006); and 98% of volunteers sampled from the Canada Games (Doherty, 2009) indicated that they would volunteer again after a positive experience at their respective events.…”
Section: Future Intent To Volunteermentioning
confidence: 99%